The Crack Analysis of Fatigue Tested Steel Construction - Bunda, Zbynek; Kucerova, Ludmila; Kepka, Miloslav (Manufacturing Technology Journal, 2019)
Laboratory fatigue testing is an important part of the fatigue design of machine components that are supposed to work under cyclic loading. These tests are used to confirm whether the tested component matches the required fatigue life and they also serve as a verification of the numerical calculations. This paper describes a fatigue life testing of a welded steel construction. The testing was carried out in the Regional Technological Institute (RTI) using an electro-hydraulic loading system, which allows realization of the tests simulating a real service. An integral part of the fatigue tests is a pre-scheduled inspection of the crack initiation and propagation. The tested construction was checked using non-destructive magnetic particle testing before the fatigue test and also during and after the performed test. Some cracks were observed, especially in the weld area. The biggest crack had the length of approximately 40 cm. This crack was cut out and underwent detailed metallographic and fractographic analysis to estimate the effect of material purity and quality of the weld on the fracture.
Keywords: Fatigue; Magnetic Particle Testing; Fractography